Dose assessment in several accidental scenarios involving lithium leakage in three IFMIF-DONES lithium system rooms. - Martínez-Serrano, José Javier; Maestre, Jorge; Qiu, Yuefeng; Nitti, Francesco Saverio (Elsevier, 2025)
This study assesses the radiological risks from potential failures in the lithium system of the IFMIF-DONES (International Fusion Materials Irradiation Facility - Demo Oriented NEutron Source) facility, focusing on critical components in the Lithium Loop Cell (LLC), Hot Trap (H-trap), and Cold Trap (C-trap) rooms. Seven lithium leak scenarios were analyzed: four in the LLC room (near the electromagnetic pump, Target Lithium TLIC inlet/outlet, and primary heat exchanger), one in the H-trap, and one in the C-trap. Lithium release volumes varied from 0.017 m3 to 3.8 m3. Ambient dose equivalent rates, H*(10), were calculated using the MCNP 5.1.40 radiation transport code for gamma-emitting radionuclides like 7Be and activation products. Simulations included structural features affecting gamma transport, and dose maps were generated at various heights and distances from leaks. The most severe radiological conditions arose from the Primary Heat Exchanger (PHX) rupture and Ctrap leakage, with peak H*(10) rates of 94 mSv/h and 130 mSv/h, respectively. To meet annual dose limits (50 mSv/year), maximum allowable human intervention times ranged from 32 min (PHX rupture) to 714 min (Htrap failure). Post-leak access to the C-trap room is prohibited due to exceeding red zone thresholds. These results are essential for safety planning, remote handling, and accident mitigation strategies within the IFMIF-DONES lithium loop systems.
Keywords: Instalaciones nucleares - Medidas de seguridad; Fuentes de radiación; Litio; Dosimetría; IFMIF-DONES; Gamma dose; Activated corrosion products; Lithium system; Lithium leakage